Analisis Metode Forward Chaining Pada Sistem Pakar Diagnosa Penyakit Hewan Sapi Berbasis Android - Putra, Fajar R. B; Fadlil, Abdul; Umar, Rusydi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
In particular, Sorong Regency, West Papua, where the availability of veterinarians is still relatively low. The problems that occur in the regency make it difficult for experts to deal with a disease that occurs in livestock, especially cattle. This also makes it difficult for people to diagnose certain diseases experienced by their livestock, so that handling becomes slow and resulting in the risk of death for livestock. This research aims to create an application system to diagnose cattle disease base on android to make it easier for breeders to diagnose symptoms of a disease that occurs in their cattle (cow). The process carried out is by interviewing experts consisting of three paramedics, the results obtained are in the form of disease data, symptoms, and solutions which are used as data on the system. The data that has been analyzed using the Forward Chaining method results in an android-based expert system, help breeders’ difficulties in diagnosing cattle diseases. The results obtained are that the system created to produce a disease that is in accordance with the exiting symptoms. The system is very helpful for farmers in Sorong Regency, they hope that ini the future the system can be updated if there are new diseases or symptoms. The data provided by animal husbandry department and experts are very helpful in this research.`